2019
DOI: 10.2196/14408
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Mobile Health Tool Versus a Paper Action Plan to Support Self-Management of Chronic Obstructive Pulmonary Disease Exacerbations: Randomized Controlled Trial

Abstract: BackgroundMany patients with chronic obstructive pulmonary disease (COPD) suffer from exacerbations, a worsening of their respiratory symptoms that warrants medical treatment. Exacerbations are often poorly recognized or managed by patients, leading to increased disease burden and health care costs.ObjectiveThis study aimed to examine the effects of a smart mobile health (mHealth) tool that supports COPD patients in the self-management of exacerbations by providing predictions of early exacerbation onset and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 29 publications
(47 reference statements)
0
84
0
2
Order By: Relevance
“…When gender distribution was analysed, 55.6% (1,212) of patients were males. Five studies included patients with stage I‐IV COPD (Aboumatar et al., 2018; Billington et al., 2015; Bischoff et al., 2012; Boer et al., 2019; Kuo et al., 2013). Remaining studies ( N = 7) were confined to COPD patients with stage II‐IV ( N = 2), II‐III ( N = 2), I‐III ( N = 2) or only III COPD ( N = 1) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When gender distribution was analysed, 55.6% (1,212) of patients were males. Five studies included patients with stage I‐IV COPD (Aboumatar et al., 2018; Billington et al., 2015; Bischoff et al., 2012; Boer et al., 2019; Kuo et al., 2013). Remaining studies ( N = 7) were confined to COPD patients with stage II‐IV ( N = 2), II‐III ( N = 2), I‐III ( N = 2) or only III COPD ( N = 1) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The content of SM programs consisted of detailed information on COPD including anatomical structures of respiratory ways and lung, pathophysiology, common symptoms, progress and disease stages ( N = 12), conventional medications ( N = 12), exacerbation management ( N = 12), daily exercises ( N = 9) and breathing retraining ( N = 9). Moreover, seven studies focused on lifestyle changes (Aboumatar et al., 2018; Bischoff et al., 2012; Boer et al., 2019; Bucknall et al., 2012; Chang & Dai, 2019; Jonsdottir et al., 2015; Walters et al., 2013) and seven studies gave training on smoking cessation (Aboumatar et al., 2018; Chang & Dai, 2019; Jolly et al., 2018; Jonsdottir et al., 2015; Kuo et al., 2013; LianHong, Yan, LingYun, Li, & YongMei, 2019; Walters et al., 2013). Moreover, seven studies trained patients about coping with anxiety–stress (Billington et al., 2015; Bischoff et al., 2012; Boer et al., 2019; Bucknall et al., 2012; Jonsdottir et al., 2015; Song et al., 2014; Walters et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The results were favorable in terms of adopting positive habits in self-care and from the patients’ point of view, about the support they received in clinical, social, and therapeutic guidance. Some recent studies, such as by Boer and colleagues [ 47 ], highlighted patients’ perception of the usability and support offered by mHealth systems. However, as in some of the studies reviewed [ 48 ], the therapeutic educator reported an increased workload compared with studies of periodic calls or more time-spaced follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported positive results on some quality of life measures and symptoms [ 10 , 33 - 35 ], but many have reported no effects [ 8 , 12 , 36 - 39 ]. With respect to health care utilization, the effects are also mixed, with some reporting reductions in hospitalizations [ 5 , 7 , 33 , 40 - 42 ], length of stay [ 7 , 33 , 40 , 43 ], and ED visits [ 33 , 40 ], but many failing to find significant effects [ 6 , 10 , 34 , 36 - 38 ]. A recent systematic review concluded that the evidence on the effectiveness of remote monitoring is mixed [ 16 ], although some meta-analyses have reported significant reductions in hospitalizations and ED visits [ 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that action plans can be effective in reducing the effects of exacerbations when they are followed, but few patients follow written action plans [ 45 ]. The integration of action plans within the platform, with patients receiving feedback directly from the device, may improve their use, although a recent study found no additional benefits when action plans were embedded within a self-monitoring mobile app over those provided by a written action plan [ 38 ]. Further developments in trend analyses and predictive analytics of remote monitoring data [ 46 ] may allow for early detection of exacerbations as relative changes in vital signs may be more important than detecting vitals reaching absolute thresholds.…”
Section: Discussionmentioning
confidence: 99%